DEVELOPED TACTICS OF COMPLEX TREATMENT OF FOOT MYCOSES AMONG WORKERS OF RAILWAY TRANSPORT - Мамедов, К.А. (World of Medicine and Biology, 2017)
Objective: to study the clinical and epidemiological features of foot mycoses in workers of railway transport in Azerbaijan.Methods. The study included 110 patients with mycoses of the feet, in age from 20 to 65 years from 2009 to 2013. Among the examined patients there were 42 women and 68 men. In the main group were analyzed: complaints (burning sensation of feet skin, itching, pain when walking, skin lesions stop), discomfort, medical history (risk factors, disease duration, conducted earlier treatment, possible source of infection), objective clinical symptoms (maceration of the epidermis, erythema, erosion, flaking, surface and deep cracks, vesicles, papules) in dynamics, the data laboratory tests before treatment, during treatment and after treatment ( respectively 7, 14 and 21 days). To study the condition of the skin defined the main functional indicators of the condition of the skin: oiliness, moisture, and acidity of the skin of the feet. The measurement was carried out using the Multi skin test center MC 750 (Courage+ Khazaka Electronic GMBH.) made in Germany. For quantitative assessment of functional values of skin parameters was calculated the index of the corresponding functional state of the skin (IFSK). Results.To identify features of the course and outcomes of foot mycoses (MS) we carried out the analysis of morbidity in 110 MS patients. All laboratory tests from 110 patients with MS were carried out in dynamics before and after treatment. The control group consisted of 29 healthy individuals (19 male (65,5±5.2%) and 10 women (34,5±5.2 percent). Mycotic infection was diagnosed in 110 (65,5±1.3 percent) of the 168 surveyed railway workers. Comprehensive treatment of traditional therapy (desensitizing, antihistamines, vitamin therapy) and enzyme therapy (Wobenzyme) conducted among 28 patients with acute MS and 40 patients with chronic MS. Just recovered 61 (89,7+3,7%) patients, including 37( 92,8+4.0%) of patients with chronic and 24 (85,6+6,6%) patients with the acute form of MS (χ2=1,32, p>0.05). Comprehensive treatment of foot mycoses, including antihistamines and desensitizing therapy, vitamin therapy, enzyme therapy (Wobenzyme) and eubiotics Bifidumbacterin-L, and is directed on correction of violations of metabolism and immune status allows you to achieve full cure at 83.3+5.8% of cases.Conclusion. The treatment of MS, carried out comprehensively, according to the professional status, also use advanced treatment of concomitant underlying disease pathology and to include not only etiotropic treatment, but also corrective change medications.
Keywords: mycosis of the feet; professional dermatoses; systemic antimycotic